Perceptions and attitudes of the local people towards bats in the surroundings of the Escaba dam (Tucumán, Argentina) - Castilla, María Cecilia; Campos, Claudia; Colantonio, Sonia; Díaz, Monica (Ethnobiology and Conservation, 2020)
When biodiversity conservation of non-charismatic species is a priority, local people perception and value attributed to species are of vital importance. The presence of a huge colony of bats (Tadarida brasiliensis) in the Escaba dam located at the Yungas forest is an emblematic case for the conservation of bats in Argentina. The objective of this study was to evaluate the perception and attitude about the bats of the people living around the Escaba dam in order to redirect conservation efforts and education plans. Semi-structured surveys and participant observation were used to survey the information; and generalized linear models to analyze. The local inhabitants do not recognize the diversity of bat species, and mention only blood-sucking and insectivorous bats. The results show a positive trend in perception and attitude, influenced by the recognition of the role of bats as insect controllers and a feeling of identity generated by the colony. The perception becomes more positive as age advances and in those who reached the secondary level of education. New ways of measuring perception and attitude are presented, such as describing the forms of bat exclusion. All this must be taken into account in the development of the management plan, which should consider the possible local use of guano as a fertilizer, sustainable tourism and educational actions aiming at differentiating the species (i.e. this is not an hematophagous bat colony), the role of the colony at controlling possible diseases and the ecosystem services associated with these species.